INELIGIBILITY BY ILLITERACY: A LEGAL STUDY AND SOCIAL ON POLITICAL EXCLUSION IN BRAZIL (CIPEEX, 2025)
This study analyzes the eligibility conditions provided for in the Federal Constitution of 1988, highlighting their legal foundations and the impacts they have on political participation and democratic legitimacy in Brazil. The central objective is to understand how such requirements, especially the requirement of literacy, act both as instruments of institutional strengthening and as barriers to political exclusion that mainly affect vulnerable groups. The methodology used was qualitative, based on bibliographic and documentary research, with examination of the Constitution of the Federative Republic of Brazil, relevant infraconstitutional legislation, jurisprudence of the Superior Electoral Court (TSE) and specialized doctrine of authors such as José Jairo Gomes, Alexandre de Moraes, José Afonso da Silva and Carlos Blanco de Morais. The results indicate that the constitutional criteria of Brazilian nationality, full exercise of political rights, electoral enlistment, residence in the district, party affiliation and minimum age play a fundamental role in the legitimization of the electoral process, ensuring legal, political and social ties between the candidates and the community they intend to represent. However, the requirement that the candidate is not illiterate, although not expressly provided for as a cause of ineligibility, has been interpreted as an implicit and necessary requirement, which, in practice, excludes millions of citizens from the political dispute. IBGE data from 2022 indicate that about 7% of the population over 15 years old remains illiterate, which corresponds to approximately 11.4 million people, showing the dimension of the social impact of this restriction. At the same time that it seeks to guarantee minimal technical aptitude for the exercise of the public function, the rule ends up disregarding the community experience and the representative capacity of individuals who, although formally illiterate, could contribute to the political life of the country. In addition, the study shows that the ordinary legislator has only the prerogative to regulate the eligibility conditions, without being able to create new requirements beyond those expressly provided for by the Constitution, under penalty of violation of the principle of strict legality. The jurisprudence of the TSE and the understanding of the Supreme Court confirm this limitation, reinforcing that the interpretation of the conditions of eligibility must respect the constitutional principles of proportionality, equality and popular sovereignty. In conclusion, the research reveals that the requirement of literacy, as well as the mandatory party affiliation, can function as a mechanism of political exclusion, restricting access to power and perpetuating historical inequalities. Although legitimized under arguments of administrative rationality and institutional strengthening, such demands end up compromising the ideal of inclusive democracy, which requires not only formal participation, but also material conditions for equitable access to the political process. Thus, it becomes urgent to rethink the compatibility of these criteria with the fundamental principles of the Democratic Rule of Law, especially the dignity of the human person, citizenship and political pluralism, in order for Brazilian democracy to move towards a more plural, fair and egalitarian representation, overcoming structural barriers that still limit effective popular sovereignty.
Keywords: Eligibility Conditions; Political Participation; Political Rights; Social Exclusion